2002
DOI: 10.1021/bp0200548
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Hydrogen Production with Immobilized Sewage Sludge

Abstract: Municipal sewage sludge was immobilized to produce hydrogen gas under anaerobic conditions. Cell immobilization was essentially achieved by gel entrapment approaches, which were physically or chemically modified by addition of activated carbon (AC), polyurethane (PU), and acrylic latex plus silicone (ALSC). The performance of hydrogen fermentation with a variety of immobilized-cell systems was assessed to identify the optimal type of immobilized cells for practical uses. With sucrose as the limiting carbon sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 29 publications
3
58
1
6
Order By: Relevance
“…It showed that activated carbon acted as a support for alginate matrix. The average of immobilized and co-immobilized beads this study is less 100 times than Wu et al(2002) [22] (Table 4). It is assumed that the microorganisms used in this study were 16.7%, the alginate material was technical, and the concentration of CaCl2 was 50%.…”
Section: Hydrogen Production Using Immobilized and Co-immobilized Beadsmentioning
confidence: 79%
See 3 more Smart Citations
“…It showed that activated carbon acted as a support for alginate matrix. The average of immobilized and co-immobilized beads this study is less 100 times than Wu et al(2002) [22] (Table 4). It is assumed that the microorganisms used in this study were 16.7%, the alginate material was technical, and the concentration of CaCl2 was 50%.…”
Section: Hydrogen Production Using Immobilized and Co-immobilized Beadsmentioning
confidence: 79%
“…Figure 4 shows that the hydrogen yields (mol H 2 /mol glucose) on the co-immobilized bead is larger than the immobilized bead. It is assumed that alginate stability reduced due to chelate complex compound (for example, phosphates), cells growth in the beads, as well as the evolution of gas causing pressure inside the beads will rise so that the integrity of the gel was reduced [22][28]. Although microbes growth in both beads, but the presence of activated carbon in the co-immobilized beads was stronger than the immobilization beads [22][27].…”
Section: Hydrogen Production Using Immobilized and Co-immobilized Beadsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include better handling and the repeated use of cells as well as improved solid to liquid separation efficiency [16]. Immobilized cell culture systems for the continuous production of hydrogen using pure and mixed cultures have been reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%